MONGONDOW STRENGTHENING ORAL TRADITIONS: LITERATURE AND PERFORMING ARTS IN THE LOCAL LANGUAGE OF BOLAANG MONGONDOW - Rolany Rambing, Rosalina; Lumempouw, Femmy (JURNAL ILMU BUDAYA, 2024)
Research on strengthening oral traditions is very important to do because literary products in oral form have been found less. Researchers who conduct research related to this local wisdom will contribute to the community itself as support in the field of art and culture and support tourism and creative economy in Bolaang Mongondow. This research is a continuation from 2022 which is located in the Minahasa area. Research to be carried out in 2023 on: Strengthening Oral Traditions: Literature and Performing Arts as an Effort to Preserve Regional Language and Traditional Cultural Values of the Bolaang Mongondow Community.